Comparative Analysis of the Operation Control System for High-speed Maglev and the CBTC Signal System for Metro - WU Weiping; HU Jian; GAO Yuan (Kongzhi Yu Xinxi Jishu)
The backbone of high-speed maglev system is the operation control system (OCS), which is responsible for train control and operation safety. In order to provide theoretical basis for further research and to better understand the key features of OCS, comparative researches were made between CBTC (communication based train control) system and the OCS from different aspects including system framework, routing, etc. Through comparative analysis, it can accelerate system devolopment based on part of CBTC technology and related concepts.